Minat Membaca Puisi Universitas Lambung Mangkurat, Jurusan Pendidikan Bahasa dan Sastra Indonesia - Agnia Fitri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explain the level of student interest and various aspects that influence their interest in reading poetry among students of the Department of Indonesian Language and Literature Education, Lambung Mangkurat University (ULM) class of 2024. The research focuses on how students interpret poetry, factors that encourage and inhibit reading interest, and the role of the academic environment in shaping literary appreciation, especially poetry. This study uses a descriptive qualitative approach through interviews and documentation to gain an in-depth understanding of students' experiences, views, and habits in reading poetry. The results show that students' interest in poetry is in the moderate category. Some students consider poetry to be beautiful and meaningful works, thus helping them to reflect on themselves and increase their interest in reading. However, others find it difficult to understand the implied meaning in poetry and consider poetry a complicated and less interesting genre. Factors that encourage interest in reading poetry include the active role of lecturers in presenting interesting poetry material, campus literary activities such as poetry readings and competitions, and the existence of student communities that focus on writing and literary appreciation. Meanwhile, obstacles found include limited literacy facilities such as reading rooms and poetry book collections, low student personal motivation, and the dominance of digital media which is more practical and entertaining than printed literary works. This research emphasizes the importance of creative learning strategies and support for campus activities to revitalize the culture of reading poetry so that literary appreciation can develop more optimally.